Shear Stress Counteracts Endothelial CX3CL1 Induction and Monocytic Cell Adhesion - Aaron Babendreyer; Lisa Molls; Daniela Dreymueller; Stefan Uhlig; Andreas Ludwig (Hindawi Limited, 2017)
Flow conditions critically regulate endothelial cell functions in the vasculature. Reduced shear stress resulting from disturbed blood flow can drive the development of vascular inflammatory lesions. On endothelial cells, the transmembrane chemokine CX3CL1/fractalkine promotes vascular inflammation by functioning as a surface-expressed adhesion molecule and by becoming released as soluble chemoattractant for monocytic cells expressing the receptor CX3CR1. Here, we report that endothelial cells from human artery, vein, or microvasculature constitutively express CX3CL1 when cultured under static conditions. Stimulation with TNFα under static or very low shear stress conditions strongly upregulates CX3CL1 expression. By contrast, CX3CL1 induction is profoundly reduced when cells are exposed to higher shear stress. When endothelial cells were grown and subsequently stimulated with TNFα under low shear stress, strong adhesion of monocytic THP-1 cells to endothelial cells was observed. This adhesion was in part mediated by transmembrane CX3CL1 as demonstrated with a neutralizing antibody. By contrast, no CX3CL1-dependent adhesion to stimulated endothelium was observed at high shear stress. Thus, during early stages of vascular inflammation, low shear stress typically seen at atherosclerosis-prone regions promotes the induction of endothelial CX3CL1 and monocytic cell recruitment, whereas physiological shear stress counteracts this inflammatory activation of endothelial cells.